(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
This paper provides an overview of data warehouse systems development and production tools. It also contains tools evaluation methodology. There are four types o f tools used in data warehouse environment. The group of unique criteria is used for every tool evaluation. Each criterion has its own severity (critical, important, additional). Project specific features, chosen criteria set and its severity is a base for tools evaluation matrix. In addition, the unique criteria set for each type o f tools is developed and described in this paper.The results of research are used in Latvia State Revenue Service data warehouse system development.